2020
DOI: 10.1177/0272431620961459
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence of Positive Youth Constructs and Purpose Development: Results From a Qualitative Approach

Abstract: This study investigates how adolescents begin to demonstrate skills and approaches that help them pursue their aspirations. The qualitative study examined emergent forms of key indicators of adolescent thriving: the 5Cs of positive youth development and sense of purpose. Pre- and post-program interviews with 24 S2 (~seventh grade) Scottish adolescents who participated in a school-based character program explored the presence, absence, and elucidations of each of the 5Cs as well as their conceptualizations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This study proposed precontemplation, foreclosure, ruminative exploration, and diffusion as additional developmental stages in the formation of meaning in life. Previous studies using cluster analysis methods have identified four developmental states of meaning in life: accomplished, foreclosed, uncommitted, and diffused, which supports our proposed stage classification [13,16,17].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study proposed precontemplation, foreclosure, ruminative exploration, and diffusion as additional developmental stages in the formation of meaning in life. Previous studies using cluster analysis methods have identified four developmental states of meaning in life: accomplished, foreclosed, uncommitted, and diffused, which supports our proposed stage classification [13,16,17].…”
Section: Discussionsupporting
confidence: 84%
“…Third, some adolescents may be in a state of "ruminative exploration" in which they do not know what to do until they know what they want to do. Some researchers have qualitatively used cluster analysis to investigate the division of meaning based on Marcia's findings [13][14][15][16][17]. It is important to note that cluster analysis can help identify discrete subgroups of people with different levels of public engagement within a given sample.…”
Section: Meaning In Lifementioning
confidence: 99%
See 2 more Smart Citations
“…School curriculum support through preventive programmes is another significant form of PYD implementation. Inspire Aspire (IA) is promoting awareness of character development by creating educational experiences for youth that foster honesty, generosity, reliability, forward-looking activity, diligence, thrift, joy, purpose, curiosity, and humility (Tevington et al, 2020). Positive Adolescent Training through Holistic Social programmes (PATHS to Adulthood) is another example implemented on a large scale in schools (Shek & Sun, 2009).…”
mentioning
confidence: 99%